2005
DOI: 10.1001/archneur.62.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal vs Subthalamic Nucleus Deep Brain Stimulation in Parkinson Disease

Abstract: Background: Deep brain stimulation (DBS) of the globus pallidus interna (GPi) and subthalamic nucleus (STN) has been reported to relieve motor symptoms and levodopa-induced dyskinesia in patients with advanced Parkinson disease (PD). Although it has been suggested that stimulation of the STN may be superior to stimulation of the GPi, comparative trials are limited. Objective: To extend our randomized, blinded pilot comparison of the safety and efficacy of STN and GPi stimulation in patients with advanced PD. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
361
2
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(385 citation statements)
references
References 32 publications
(12 reference statements)
11
361
2
4
Order By: Relevance
“…DBS of the STN is most often performed bilaterally, although unilateral DBS of STN or GPi can be highly effective in some cases of asymmetric parkinsonism. In most patients, DBS alleviates parkinsonian motor signs, shortens 'off' periods, and reduces druginduced dyskinesias, dystonia, and motor fluctuations (Rodriguez-Oroz et al, 2004;Anderson et al, 2005;Weaver et al, 2005;Portman et al, 2006;Bronstein et al, 2011). In general, both GPi-and STN-DBS are more effective than medical management alone to alleviate motor deficits in patients with advanced PD (Just and Ostergaard, 2002;Martinez-Martin et al, 2002;Troster et al, 2003;Lezcano et al, 2004;Diamond and Jankovic, 2005;Erola et al, 2005;Halbig et al, 2005;Lyons and Pahwa, 2005;Deuschl et al, 2006;Rodrigues et al, 2007a, b;Montel and Bungener, 2009;Weaver et al, 2009b;Zahodne et al, 2009).…”
Section: Current Surgical Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS of the STN is most often performed bilaterally, although unilateral DBS of STN or GPi can be highly effective in some cases of asymmetric parkinsonism. In most patients, DBS alleviates parkinsonian motor signs, shortens 'off' periods, and reduces druginduced dyskinesias, dystonia, and motor fluctuations (Rodriguez-Oroz et al, 2004;Anderson et al, 2005;Weaver et al, 2005;Portman et al, 2006;Bronstein et al, 2011). In general, both GPi-and STN-DBS are more effective than medical management alone to alleviate motor deficits in patients with advanced PD (Just and Ostergaard, 2002;Martinez-Martin et al, 2002;Troster et al, 2003;Lezcano et al, 2004;Diamond and Jankovic, 2005;Erola et al, 2005;Halbig et al, 2005;Lyons and Pahwa, 2005;Deuschl et al, 2006;Rodrigues et al, 2007a, b;Montel and Bungener, 2009;Weaver et al, 2009b;Zahodne et al, 2009).…”
Section: Current Surgical Targetsmentioning
confidence: 99%
“…Most neurosurgeons currently prefer the STN over the GPi as a target for DBS in PD, because of the perceived greater antiparkinsonian benefit of STN-DBS (Anderson et al, 2005;Moro et al, 2010). However, there is no clear evidence that the STN is, in fact, a better target than GPi.…”
Section: Stn Vs Gpi As Targets For Dbs In Pd?mentioning
confidence: 99%
“…However, other early studies comparing STN and GPi DBS targets reveal increased adverse cognitive and behavioral effects after STN DBS. 8,196 Speculation as to the potential cause of cognitive decline in early versus more recent studies may stem from the close anatomical apposition of motor, associative, and limbic pathways in the STN. As targeting techniques have improved, side effects of stimulation of these nonmotor pathways may have decreased.…”
Section: Cognitive Effects Of Dbs In the Pd Populationmentioning
confidence: 99%
“…Studies by Merello et al 15 and Fields et al 81 found the cognitive safety of GPi DBS and pallidotomy to be comparable. Although some suggest that bilateral GPi DBS may entail less cognitive morbidity than bilateral STN DBS, 27,74,82 the only randomised comparison of the cognitive effects of GPi and STN DBS has failed to reveal substantial differences between the two treatments. 57 A larger randomised trial comparing the effects Parkinson's Disease More out of levodopa.…”
Section: Pallidal Versus Subthalamic Deep Brain Stimulationmentioning
confidence: 99%